Urgensi Mempelajari Rasm Al-Qur’an Di Era Modern - Umar Al Faruq; Dinar Dania Al Kautsar; Putri Farhanah; Abyan Al Faros; Lana Najma Fairuza (CV. ITTC INDONESIA, 2024)
This article explains in depth the urgency or importance of studying the rasm of the Qur'an in the modern era or today because the rasm of the Qur'an is Ulumul Qur'an or the discipline of the Qur'an that describes how the systematics of writing letters or lafadz in writing the Qur'an and the various rasm of the Qur'an how it relates to the science of Qira'at Qur'an and also its urgency for us to understand this discipline in this fast-paced and digital era or better known as the modern era. This article uses the Library Research method or library study or research which is carried out in the library by reviewing books, articles, journals and other sources of literature or reading. And it was found that there are three types of Rasm Qur'an, namely Rasm Qiyasi, Rasm Arudi and Rasm Utsmani, and also found a relationship or connection with the science of Qira'at Qur'an.